INFLATION IN THE UNITED KINGDOM IN TIMES OF WAR AND PANDEMIC (A SOLUTION FROM THE ISLAMIC ECONOMICS) - Talha Ayub; Martini Dwi Pusparini (IAIN Manado, 2022)
History discloses that economic turbulence is not merely caused by economic failures such as policies, institutions, or market conditions, there are also a few phenomenon that contributes to a robust impact on the economic decline namely war and pandemics. The purpose of this paper is to reveal the economic downturn such as inflation in the United Kingdom caused by the covid-19 pandemic and worsened by the war between Russia and Ukraine. This paper also proved that the Islamic economic system is a solution to attaining a prosperous economy for society. Using qualitative research through descriptive analysis, this paper analyzed how the Islamic economic system possesses a vital role in facing economic crises in times of war and pandemics. The result of this paper found that Islamic economics is the only economic system that brings justice to all economic actors in the entire world, thus it leads to forming healthy economic circumstances and then avoiding the economic crisis to occur.